Female Urethral Cavernous Hemangioma, A Rare Entity: Two Case Reports and Review of The Literature - Sharifiaghdas, Farzaneh; Mahmoudnejad, Nastaran; Rostaminezhad, Niloofar; Parvin, Mahmoud (Urology Journal, 2019)
Genitourinary hemangiomas are very rare. To our knowledge few cases of female urethral hemangiomas have been reported and presenting cases are the first reports in Iran. They should be considered as differential diagnosis of any female patient with microscopic or gross hematuria or bloody urethral discharge, especially when other parts of urinary system are radiologically intact. Thorough physical examination of genital area is highly recommended in order not to miss any urethral lesions. Herein we report two cases of female urethral cavernous hemangioma, their management and a review of literature.